Long noncoding RNA MALAT-1 is a new potential therapeutic target for castration resistant prostate cancer - Ren, Shancheng; Liu, Yawei; Xu, Weidong; Sun, Yi; Lu, Ji; Wang, Fubo; Wei, Min; Shen, Jian; Hou, Jianguo; Gao, Xu; Xu, Chuanliang; Huang, Jiaoti; et al. (The Journal of urology, 2013)
To understand the role of MALAT-1 in prostate cancer we evaluated its expression in prostate cancer tissues and cell lines. We also studied the therapeutic effects of MALAT-1 silencing on castration resistant prostate cancer cells in vitro and in vivo. Quantitative reverse transcriptase-polymerase chain reaction was used to detect MALAT-1 expression in prostate cancer tissues and cell lines. siRNA against MALAT-1 was designed and the silencing effect was examined by quantitative reverse transcriptase-polymerase chain reaction. The biological effects of MALAT-1 siRNA on cells were investigated by examining cell proliferation using a cell counting kit and cell colony assays as well as cell migration by in vitro scratch assay, cell invasion by Transwell® invasion assay and cell cycle by flow cytometry. We further investigated the effect of therapeutic siRNA targeting MALAT-1 on castration resistant prostate cancer in vivo. MALAT-1 was up-regulated in human prostate cancer tissues and cell lines. Higher MALAT-1 expression correlated with high Gleason score, prostate specific antigen, tumor stage and castration resistant prostate cancer. MALAT-1 down-regulation by siRNA inhibited prostate cancer cell growth, invasion and migration, and induced castration resistant prostate cancer cell cycle arrest in the G0/G1 phases. Importantly, intratumor delivery of therapeutic siRNA targeting MALAT-1 elicited delayed tumor growth and reduced metastasis of prostate cancer xenografts in castrated male nude mice, followed by the concomitant prolongation of survival of tumor bearing mice. MALAT-1 may be needed to maintain prostate tumorigenicity and it is involved in prostate cancer progression. Thus, MALAT-1 may serve as a potential therapeutic target for castration resistant prostate cancer.